Public Procurement Principles Compliance and Value for Money in the Procurement Process of Uganda’s Local Governments; a Case of Mbale District Local Government - James Daada (Uganda Christian University, 2024)
The aim of the study was to examine the effect of public procurement principles compliance on value for money in the procurement process of Uganda’s local governments. The specific objectives of the study were: To evaluate the relationship between Mbale District Local Government’s compliance with the accountability principle and value for money in the public procurement process: To examine the relationship between Mbale District Local Government’s compliance with the competition principle and value for money in the public procurement process: To evaluate the relationship between Mbale District Local Government’s compliance with the confidentiality principle and value for money in the public procurement process. The case study used designed questionnaires to collect data from a sample of 96 respondents. Quantitative data was analyzed using the SPSS computer-based software, employing both descriptive and inferential techniques, while qualitative data was summarized into themes and quotes. The study found that the transparency principle was significant in predicting value for money, with an R square value and a regression coefficient (Beta = -0.218, p value = 0.202). This indicated that the transparency principle had a positive and significant impact on predicting value for money. Furthermore, the accountability principle showed an R square value of 0.314 and a regression coefficient (β = 0.218, p value = 0.202), signifying a positive and significant effect on value for money. Additionally, the competition principle had a significant effect on predicting value for money, with p-values of 0.000 (less than 0.05), and an R square value of 0 (Beta = -0.194, p value = 0.227). The study concluded that value for money improves with better budgetary management. It recommended that Mbale District Local Government should ensure that the Procurement and Disposal Unit (PDU) adheres to public procurement principles while undertaking the procurement process. Failure to comply with these principles should result in punishments for all those involved.
Undergraduate research